The Role of The Comprehensive Quality Strategy in The Economic Enterprise to Achieve Sustainable Development - rais, mabrouk; DAOUD , MOUNIR (Journal of Social Sciences and Humanities, 2023)
The aim of this study is to highlight the means of achieving sustainability for economic institutions by relying on the approach of Total Quality Management (TQM). The purpose of this study is to shed light on the concept of TQM as a strategic philosophy adopted by institutions to achieve sustainable development, as well as to highlight various concepts related to sustainable development. It aims to demonstrate its ability to equip economic institutions with the capability to face all economic, social, and environmental challenges, and to uncover various methods and strategies for TQM while emphasizing all international standards and ISO specifications that enable and facilitate sustainable development in the economic institution. In our study, we employ the descriptive-analytical method, which provides us with detailed data. We have concluded that adopting the TQM strategy in the economic institution leads to achieving sustainable development.